RESEARCH TRENDS ON CHARACTER EDUCATION AND INTERACTIVE LEARNING MULTIMEDIA IN ELEMENTARY SCHOOL: A BIBLIOMETRIC ANALYSIS - Mochammad Miftachul Huda; Sapriya Sapriya; Wahyu Sopandi (Universitas Majalengka, 2025)
Using VOSviewer software, this study aims to determine research trends by conducting bibliometric analysis mapping of articles obtained from Google Scholar on the topic of character education and interactive learning multimedia in elementary schools. The keywords